2011
DOI: 10.1159/000335294
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Pulsating Cupping (Pneumatic Pulsation Therapy) for Chronic Neck Pain

Abstract: Background: Pneumatic pulsation therapy may combine the effects of cupping therapy and massage. This study investigated the effect of pneumatic pulsation therapy on chronic neck pain compared to standard medical care. Methods: 50 patients (79.15% female; 46.17 ± 12.21 years) with chronic nonspecific neck pain were randomized to treatment group (TG; n = 25) or control group (CG; n = 25). The TG received 5 pneumatic pulsation treatments over a period of 2 weeks utilizing a mechanical device. Treatment was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 37 publications
3
75
0
2
Order By: Relevance
“…A trial at the University of Essen studied the effect of dry traditional as well as pulsatile dry cupping in chronic neck pain. Statistically significant and clinically relevant effects of cupping compared to waiting-list control were found after 5 sessions of dry cupping with both methods [10,11], but also an effect of traditional cupping on pain and quality of life already after one cupping session has been observed in this trial [12]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A trial at the University of Essen studied the effect of dry traditional as well as pulsatile dry cupping in chronic neck pain. Statistically significant and clinically relevant effects of cupping compared to waiting-list control were found after 5 sessions of dry cupping with both methods [10,11], but also an effect of traditional cupping on pain and quality of life already after one cupping session has been observed in this trial [12]. …”
Section: Discussionmentioning
confidence: 95%
“…However, recent clinical studies have reported positive results of cupping in patients with musculoskeletal diseases e.g. lower back pain [6], carpal tunnel syndrome [7], brachialgia paresthetica nocturna [8], cancer pain [9] and chronic neck pain [10-12]. In China Cupping is widely used and two systematic reviews were recently published about the results [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 27 studies were excluded, as they did not have sufficient data for inclusion. Of these, 10 randomized trials were included in the systematic review and meta-analysis (23,(26)(27)(28)(29)(30)(31)(32)(33)(34). The search strategy and method of study selection is defined in Figure 1.…”
Section: Studies Descriptionmentioning
confidence: 99%
“…All studies adopted a two-armed parallel group design. Changes of VAS as the primary outcome of study were reported in 5 trials (26,(28)(29)(30)32). Six trials calculated the change in the Neck disability index (NDI) (23,26,28,(30)(31)(32).…”
Section: Studies Descriptionmentioning
confidence: 99%
See 1 more Smart Citation